Leaf temperatures mediate alpine plant communities' response to a simulated extended summer. Issue 3 (28th December 2018) - Wentz, Katherine F.; Neff, Jason C.; Suding, Katharine N.
Abstract: We use a quantitative model of photosynthesis to explore leaf‐level limitations to plant growth in an alpine tundra ecosystem that is expected to have longer, warmer, and drier growing seasons. The model is parameterized with abiotic and leaf trait data that is characteristic of two dominant plant communities in the alpine tundra and specifically at the Niwot Ridge Long Term Ecological Research Site: the dry and wet meadows. Model results produce realistic estimates of photosynthesis, nitrogen‐use efficiency, water‐use efficiency, and other gas exchange processes in the alpine tundra. Model simulations suggest that dry and wet meadow plant species do not significantly respond to changes in the volumetric soil moisture content but are sensitive to variation in foliar nitrogen content. In addition, model simulations indicate that dry and wet meadow species have different maximum rates of assimilation (normalized for leaf nitrogen content) because of differences in leaf temperature. These differences arise from the interaction of plant height and the abiotic environment characteristic of each plant community. The leaf temperature of dry meadow species is higher than wet meadow species and close to the optimal temperature for photosynthesis under current conditions. As a result, 2°C higher air temperatures in the future will likely lead to declines in dry meadow species' carbon assimilation. On the other hand, a longer and warmer growing season could increase nitrogen availability and assimilation rates in both plant communities. Nonetheless, a temperature increase of 4°C may lower rates of assimilation in both dry and wet meadow plant communities because of higher, and suboptimal, leaf temperatures. Abstract : We use a quantitative model of photosynthesis to explore leaf‐level limitations to plant growth in an alpine tundra ecosystem that is expected to have longer, warmer, and drier growing seasons. Model simulations indicate that dry and wet meadow species have different rates of assimilation (normalized for leaf nitrogen content) in an extended summer because of differences in the leaf temperature. These differences arise from the interaction of plant height and the abiotic environment characteristic of each plant community.